Negro intelectual, intelectual negro ou negro-intelectual: considerações do processo de constituir-se negro-intelectual - Oliveira, Evaldo Ribeiro (2013)
This research entitled "Black Intellectual, Intellectual Black or Black-Intellectual: notes of the process of becoming Black-intellectual", aimed at understanding processes in which Black men and women have made himself / herself in intellectual and identify their experiences of men and women Blacks to form up and intellectuals can contribute to the education of ethnic-racial relations. For this purpose, I make the use of the research question: What processes are present in the form themselves as Black intellectuals? The methodology of the present research is based on principles of Phenomenological that inspires the researcher's stance in relation to the object of research, the research participants, the processes of collecting, analyzing and interpreting data. There were three in-depth conversations with professionals, self-identified Blacks, recognized as intellectuals, with the goal of understanding the meanings of processes experienced by Black men and women as they constitute intellectual. The research allowed an understanding that to constitute themselves as Black and as intellectual, there is a mutual strengthening of both: the Black person and the community to which they belong. Also identified not only studies schools and universities as places of education but also family influences, sensitivity to perceive and study social realities that affect Blacks and especially coexistence and fights with the Black Movement. The Black intellectuals seek to act in the community, in dialogue with the Black community, with other intellectuals and society in general. Its education proceeds in the following dimensions: Becoming Black: a testimony of Blackness; Digging spaces: actions, reactions and joints; Definitions and ide as of who is Black intellectual; Persistence and Militancy: as if you re working out in cold iron.